Bleeding to death in a big city: An analysis of all trauma deaths from hemorrhage in a metropolitan area during 1 year. Issue 4 (October 2020) - Kalkwarf, Kyle J.; Drake, Stacy A.; Yang, Yijiong; Thetford, Caitlin; Myers, Lauren; Brock, Morgan; Wolf, Dwayne A.; Persse, David; Wade, Charles E.; Holcomb, John B.
Abstract : BACKGROUND: Hemorrhage is the most common cause of potentially preventable trauma deaths, but no studies have focused on all civilian traumatic deaths from hemorrhage, so we describe a year of these deaths from a large county to identify opportunities for preventing hemorrhagic deaths. METHODS: All trauma-related deaths in Harris County, Texas, in 2014 underwent examination by the medical examiner; patients were excluded if hemorrhage was not their primary reason for death. Deaths were then categorized as preventable/potentially preventable hemorrhage (PPH) or nonpreventable hemorrhage. These categories were compared across mechanism of injury, death location, and anatomic locations of hemorrhage to determine significant differences. RESULTS: A total of 1, 848 deaths were reviewed, and 305 were from uncontrolled hemorrhage. One hundred thirty-seven (44.9%) of these deaths were PPH. Of these PPH, 49 (35.8%) occurred prehospital and an additional 28 (20.4%) died within 1 hour of arriving at an acute care setting. Of the 83 PPH who arrived at a hospital, 21 (25.3%) died at a center not designated as level 1. Isolated truncal bleeding was the source of hemorrhage in 102 (74.5%) of the PPH. Of those who died with truncal PPH, the distribution was 22 chest (21.6%), 39 chest and abdomen (38.2%), 16 abdomen (15.7%), and 25 all other combinations (24.5%). When patients who died within 1 hour of arrival to a hospital were combined with the 168 deaths that occurred prehospital, 223 (74.3%) of 300 deaths occurred before spending 1 hour in a hospital and 77 (34.5%) of 223 of these deaths were PPH. CONCLUSION: In a well-developed, urban trauma system, 34.5% of patients died from PPH in the prehospital setting or within an hour of hospitalization. Earlier, more effective prehospital resuscitation and truncal hemorrhage control strategies are needed to decrease deaths from PPH. LEVEL OF EVIDENCE: Therapeutic/Care management, level IV.